Bacteria assisted green synthesis of copper oxide nanoparticles and their potential applications as antimicrobial agents and plant growth stimulants - Singh, Deepak; Jain, Devendra; Rajpurohit, Deepak; Jat, Gajanand; Kushwaha, Himmat Singh; Singh, Abhijeet; Mohanty, Santosh Ranjan; Al-Sadoon, Mohammad Khalid; Zaman, Wajid; Upadhyay, Sudhir K. (Frontiers in Chemistry, 2023)
Copper oxide nanoparticles (CuO-NPs) have piqued the interest of agricultural researchers due to their potential application as fungicides, insecticides, and fertilizers. The Serratia sp. ZTB29 strain, which has the NCBI accession number MK773873, was a novel isolate used in this investigation that produced CuO-NPs. This strain can survive concentrations of copper as high as 22.5 mM and can also remove copper by synthesizing pure CuO-NPs. UV-VIS spectroscopy, DLS, Zeta potential, FTIR, TEM, and XRD techniques were used to investigate the pure form of CuO-NPs. The synthesized CuO-NPs were crystalline in nature (average size of 22 nm) with a monoclinic phase according to the XRD pattern. CuO-NPs were found to be polydisperse, spherical, and agglomeration-free. According to TEM and DLS inspection, they ranged in size from 20 to 40 nm, with a typical particle size of 28 nm. CuO-NPs were extremely stable, as demonstrated by their zeta potential of −15.4 mV. The ester (C=O), carboxyl (C=O), amine (NH), thiol (S-H), hydroxyl (OH), alkyne (C-H), and aromatic amine (C-N) groups from bacterial secretion were primarily responsible for reduction and stabilization of CuO-NPs revealed in an FTIR analysis. CuO-NPs at concentrations of 50 μg mL−1 and 200 μg mL−1 displayed antibacterial and antifungal activity against the plant pathogenic bacteria Xanthomonas sp. and pathogenic fungus Alternaria sp., respectively. The results of this investigation support the claims that CuO-NPs can be used as an efficient antimicrobial agent and nano-fertilizer, since, compared to the control and higher concentrations of CuO-NPs (100 mg L−1) considerably improved the growth characteristics of maize plants.